2005
DOI: 10.21236/ada436477
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Binary Compatibility with Static Compilation

Abstract: There is an ongoing debate in the Java community on whether statically compiled implementations can meet the Java specification on dynamic features such as binary compatibility. Static compilation is sometimes desirable because it provides better code optimization, smaller memory footprint, more robustness, and better intellectual property protection. Unfortunately, none of the existing static Java compilers support binary compatibility, because it incurs unacceptable performance overhead. In this paper, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The importance of binary compatibility was also recognized in the paper by Forman, et al, which they summarize as "Only application alteration necessitates recompilation" on page 430 [36] . According to Yu, et al this paper was a precursor to to Java's concept of binary compatibility [58].…”
Section: The Problem Of Fragile Abismentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of binary compatibility was also recognized in the paper by Forman, et al, which they summarize as "Only application alteration necessitates recompilation" on page 430 [36] . According to Yu, et al this paper was a precursor to to Java's concept of binary compatibility [58].…”
Section: The Problem Of Fragile Abismentioning
confidence: 99%
“…Many Java compilers that support static compilation at first ignored binary compatibility in the interest of performance; one such compiler was the GNU Java Compiler, GCJ [4]. Later research by Yu, Shao, and Trifonov showed how to support static compilation and binary compatibility [58]. These techniques were later integrated into GCJ [53].…”
Section: Binary Compatibilitymentioning
confidence: 99%
“…The Java concept of binary compatibility was first developed in SOM [36] and then later defined in the Java Language Specification (JLS) [39,58]. In Java the ABI is completely specified in The Java Virtual Machine Specification [43], thus addressing the issue of incompatible ABIs.…”
Section: Binary Compatibilitymentioning
confidence: 99%